2005
DOI: 10.1172/jci22996
|View full text |Cite|
|
Sign up to set email alerts
|

Toll-like receptor 9–induced type I IFN protects mice from experimental colitis

Abstract: Experimental colitis is mediated by inflammatory or dysregulated immune responses to microbial factors of the gastrointestinal tract. In this study we observed that administration of Toll-like receptor 9 (TLR9) agonists suppressed the severity of experimental colitis in RAG1 -/-but not in SCID mice. This differential responsiveness between phenotypically similar but genetically distinct animals was related to a partial blockade in TLR9 signaling and defective production of type I IFN (i.e., IFN-α/β) in SCID mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
231
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 397 publications
(239 citation statements)
references
References 41 publications
7
231
0
1
Order By: Relevance
“…The role we have identified for IFN-β in suppressing aspects of the TLR/NLR-driven innate inflammatory response is congruent with a significant literature detailing a homeostatic as well as anti-inflammatory role for type I IFNs in a variety of inflammatory and autoimmune conditions (34-36), particularly in the intestine (37-39). Of distinct relevance for the present study is work showing that lactic acid bacteria, a common commensal bacterium, constitutively stimulate low level production of IFN-β, but not IFN-α, in the small intestine via double-stranded RNA ligation of TLR3.…”
Section: Discussionsupporting
confidence: 85%
“…The role we have identified for IFN-β in suppressing aspects of the TLR/NLR-driven innate inflammatory response is congruent with a significant literature detailing a homeostatic as well as anti-inflammatory role for type I IFNs in a variety of inflammatory and autoimmune conditions (34-36), particularly in the intestine (37-39). Of distinct relevance for the present study is work showing that lactic acid bacteria, a common commensal bacterium, constitutively stimulate low level production of IFN-β, but not IFN-α, in the small intestine via double-stranded RNA ligation of TLR3.…”
Section: Discussionsupporting
confidence: 85%
“…Second, IFN can contribute to immune defenses against conditionally pathogenic microbiota and intestinal inflammation. Katakura and coauthors previously reported a greater sensitivity of Ifnar1-null mice to intestinal inflammation caused by dextran sodium sulfate (53). Those authors also mentioned a positive effect of IFN on the protection of barrier properties of the epithelial cell sheet in vitro.…”
Section: Discussionmentioning
confidence: 91%
“…However, TLR9 activation–mediated type 1 IFNs are protective in experimental colitis (Katakura et al, 2005). Thus PDCs may promote protection against colitis via type 1 IFN secretion.…”
Section: Discussionmentioning
confidence: 99%